Genetics of rust resistance in lentil (Lens culinaris) - and R.S. SINGH, M.P. CHAUHAN*, I.S. SINGH (Indian Phytopathology, 2002)
The genetics of rust (Uromyces viciae-fabae) resistance in lentils and the allelic relationship among resistance gene(s) in parents for utilization in breeding programmes was studied. Single crosses involving the resistant genotypes Precoz SEl, KL 86-2, L 4 136, PL 406 and PL 639 with the susceptible genotype HUL 12 were carried out. Resistance was dominant in the F1 crosses during the 2 year experiment. The pattern of F2 segregation was monogenic.